Application of Azolla for 2-Chlorophenol and 4-Chrorophenol Removal from Aqueous Solutions - Mohammad Ali Zazouli; Davoud Balarak; Yousef Mahdavi (علوم بهداشتی ایران)
Background and purpose: The 2-chlorophenol (2-CP) and 4-chlorophenol (4-CP) are phenolic compounds which may have adverse effects on human and environment. Therefore, removing these compounds from water and wastewater is necessary. This study aims to analyze 2-CP and 4-CP removal by using Azolla filiculoides biomass. Materials & Methods: Azolla biomass was sun dried, crushed and sieved to particle sizes ranging 1-2 mm. Then it was treated with 0.1M HCl for 5h followed by washing with distilled water and it was used as adsorbent. The residues concentration of 2-CP and 4-CP was measured by spectrophotometer in λmax of 274 and 280 nm, respectively. Results: The solute removed increases as contact time rises. The equilibrium time for 2-CP and 4-CP is 90 and 75, respectively. The removal efficiency of 4-CP is more than 2-CP. An increase in initial concentration of both compounds can lead to decrease of their removal efficiency. The optimum pH to remove both compounds is 5. The equilibrium data matched best on Freundlich isotherm and the adsorption kinetic model follows pseudo-second model. Conclusion: The results indicated that Azolla is an effective adsorbent for removing 2-CP and 4-CP from water and wastewater.